Optimal redistributive taxation with both labor supply and labor demand responses - Laurence Jacquet; Etienne Lehmann; Bruno Van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper characterizes the optimal redistributive tax schedule in a matching unemployment framework where (voluntary) nonparticipation and (involuntary) unemployment are endogenous. The optimal employment tax rate is given by an inverse employment elasticity rule. This rule depends on the global response of the employment rate, which depends not only on the participation (labor supply) responses, but also on the vacancy posting (labor demand) responses and on the product of these two responses. For plausible values of the parameters, our matching environment induces much lower employment tax rates than the usual competitive model with endogenous participation only.
Keywords: D82; H21; J64; 330; optimal taxation; labor market frictions; unemployment; Kalai solution